PENENTUAN PROFIL PERLAPISAN TANAH BERDASARKAN DATA SONDIRDI KOTA PONTIANAK - Maulina, Firmalisa; Priadi, Eka; Faisal, Ahmad (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2015)
The purpose of this research is to get an overview of classification and consistency according to the type of soil for each point sondir based on data sondir that party planners, implementers and technical agencies can know how much ability of soil to support the load of the building. This map can provide early information to the public if it will establish a building Pontianak city region. The target in particular is a map of the research could be used by local governments as a reference for the construction of buildings in the city of Pontianak. To achieve these targets, action has to be done is to probe the ground in Pontianak by first mengkalisifikasikan soil conditions have in common with other locations. Â  Keywords: soil classification, soil consistency, sondir.